2012
DOI: 10.1590/s1020-49892012000100007
|View full text |Cite
|
Sign up to set email alerts
|

Candida bucal en niños mexicanos con VIH/sida, desnutrición o marginación social

Abstract: The children with HIV/AIDS and malnutrition require strategies designed to reduce oral candidal colonization and reduce the risk of opportunistic infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 32 publications
(35 reference statements)
1
11
1
3
Order By: Relevance
“…Candida parapsilosis was the second most common species in the group exposed to HIV (23.07%), the third most common in the group not exposed to HIV, and was not found in samples from children with AIDS. Candida tropicalis was isolated from samples of the three groups but its prevalence was small (2.2% in the group not exposed to HIV, 5.12% in the group exposed to HIV, and 4.65% in the group with AIDS) compared with Candida albicans, C.famata, and oral colonization with pathogens that impact the overall health status of vulnerable populations, including HIVpositive children and children with AIDS 7,9 . Therefore, the aim of this study was to determine the prevalence of Candida albicans and non-albicans yeasts isolated from oral samples of children with AIDS and from children exposed and not exposed to HIV during pregnancy and treated through the public healthcare system in a city located in the interior of Bahia, Brazil.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Candida parapsilosis was the second most common species in the group exposed to HIV (23.07%), the third most common in the group not exposed to HIV, and was not found in samples from children with AIDS. Candida tropicalis was isolated from samples of the three groups but its prevalence was small (2.2% in the group not exposed to HIV, 5.12% in the group exposed to HIV, and 4.65% in the group with AIDS) compared with Candida albicans, C.famata, and oral colonization with pathogens that impact the overall health status of vulnerable populations, including HIVpositive children and children with AIDS 7,9 . Therefore, the aim of this study was to determine the prevalence of Candida albicans and non-albicans yeasts isolated from oral samples of children with AIDS and from children exposed and not exposed to HIV during pregnancy and treated through the public healthcare system in a city located in the interior of Bahia, Brazil.…”
Section: Resultsmentioning
confidence: 99%
“…are due to immunosuppression with the involvement of CD4+T lymphocytes and increased viral load as disease progresses [7][8] . Oral candidiasis is strongly indicative of the development of AIDS and may present clinical features of the pseudomembranous or erythematous forms, or their combination thereof 4,[8][9][10] . According to Domaneschi et al 4 , oral candidiasis is the most frequently observed opportunistic infection in HIV-infected children and its prevalence ranges between 20% and 72%.…”
Section: Conclusõesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the time patients were free of oral candidiasis was significantly shorter among malnourished children. Previous studies have also found malnutrition to be a systemic risk factor for the development of oral candidiasis 38,39 .…”
Section: Discussionmentioning
confidence: 95%
“…Por el contrario, concuerda con lo reportado por Gaitán-Cepeda y cols. 28 . Candida albicans fue la especie más frecuente entre los pacientes, previo al inicio de tratamiento, siendo 55,5% del total de los cultivos positivos a Candida, seguida de C. tropicalis (22,2%), similar a lo reportado en otros estudios 24,26,27,29 .…”
Section: Discussionunclassified